Exploring the hydrogen absorption and strengthening behavior in nanocrystalline face-centered cubic high-entropy alloys - Zhao, Yakai; Park, Jeong-Min; Murakami, Kotaro; Komazaki, Shin-ichi; Kawasaki, Megumi; Tsuchiya, Koichi; Suh, Jin-Yoo; Ramamurty, Upadrasta; Jang, Jae-il (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
The effect of marked change in grain size from coarse-grained to nanocrystalline can affect the hydrogen absorption and plastic deformation behavior in two face-centered cubic high-entropy alloys (HEAs), viz. equiatomic CoCrFeNi and CoCrFeMnNi. Thermal desorption analysis of the hydrogen-charged samples proved that grain boundaries act as hydrogen traps and thus largely increase the hydrogen contents in the nanocrystalline samples. A direct comparison in the hydrogen absorption between two HEAs confirms that both chemical composition and grain size are crucial factors contributing to the hydrogen solubility of the HEAs. The parameters for the thermally activated deformation from nanoindentation rate-jump tests suggest enhanced lattice friction by hydrogen, leading to a reduction in activation volume and thus modification of the plastic deformation processes. The results are discussed in two aspects, viz. the effect of grain size and chemical composition on the hydrogen-affected plastic deformation. (c) 2021 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: STRAIN-RATE SENSITIVITY; HALL-PETCH RELATIONSHIP; STACKING-FAULT ENERGY; EMBRITTLEMENT RESISTANCE; MECHANICAL-PROPERTIES; NANOINDENTATION; MICROSTRUCTURE; DEFORMATION; STABILITY; HARDNESS